Types of Euphemism in Anies Baswedan’s Speech - Barus, Jumat (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
Euphemisms are often used in language activities to subtly convey sensitive information. Careful word choice allows one to avoid using vulgar or unpleasant language that may offend others. This study aims to explain the types of euphemisms used by Anies Baswedan in his statement after the announcement of his candidacy as Indonesia's presidential candidate in the 2024 election by the Nasdem Party. Allan and Burridge's framework in categorizing the types of euphemisms becomes the theoretical basis in this research. This research uses a qualitative approach with a content analysis method, by analyzing words, phrases, or sentences containing euphemism components found in Anies Baswedan's speech on 4 October 2022, sourced from metro.tempo.co. The analysis reveals four main types of euphemisms: 11 instances of metaphor (32.35%), 6 cases of one-for-one substitution (17.65%), 16 occurrences of circumlocution (47.06%), and 1 instance of figurative expression (2.94%). These forms of euphemism are used as alternative linguistic expressions, softening the language to prevent the use of sensitive or vulgar expressions that can offend others.